FORMATION OF PEDAGOGICAL KNOWLEDGE OF FUTURE TEACHERS USING LITERATURE - Bagriy, Maria; Skydanchuk, Olena (European Science, 2022)
It is no coincidence that educational and historical themes are relevant in Western Ukrainian literature: in this way, writers-educators sought to show the indomitability of Ukrainians, the invincibility of the national "I", as well as to lift the spirit